Vacancies, Employment Outcomes and Firm Growth: Evidence from Denmark - Jesper Bagger; Francois Fontaine; Manolis Galenianos; Ija Trapeznikova (Institute of Labor Economics (IZA), 2021)
We use comprehensive data from Denmark that combine online job advertisements with a matched employer-employee dataset and a firm-level dataset with information on revenues and value added to study the relationship between vacancy-posting and various firm outcomes. Posting a vacancy is associated with a 4.5 percentage point increase in a firm's hiring rate and two-thirds of the additional hiring occurs within two months. The response of hiring from employment is twice as large as the response of hiring from non-employment. Firms that are smaller, low-wage and fast-growing are associated with larger hiring responses and that response materializes faster at larger firms, low-wage firms and fast-growing firms. We also find that separations are associated with subsequent vacancy posting and this effect is stronger for separations to employment, consistent with replacement hiring and the presence of vacancy chains. Growth in revenue and value added strongly predict vacancy-posting, with negative shocks having a stronger effect than positive shocks and larger shocks having less-than-proportional responses.
Keywords: J23; J63; 330; vacancies; hiring; separations; employment growth; firm growth; value added; revenue